The young soccer player - Lineker, Gary. (London ; New York : Dorling Kindersley, 1994)
Step-by-step photographs lead you through the rules, basic soccer skills, and special team tactics.
Includes index.
Includes World Cup 1994 team stickers.
K-3
Keywords: Soccer for children -- Juvenile literature; Soccer; Soccer